Deregulation of CRAD-controlled cytoskeleton initiates mucinous colorectal cancer via β-catenin. Issue 11 (November 2018) - Jung, Youn-Sang; Wang, Wenqi; Jun, Sohee; Zhang, Jie; Srivastava, Mrinal; Kim, Moon; Lien, Esther; Shang, Joan; Chen, Junjie; McCrea, Pierre; Zhang, Songlin; Park, Jae-Il
Abstract Epithelial integrity is maintained by the cytoskeleton and through cell adhesion. However, it is not yet known how a deregulated cytoskeleton is associated with cancer. We identified cancer-related regulator of actin dynamics (CRAD ) as frequently mutated or transcriptionally downregulated in colorectal cancer. We found that CRAD stabilizes the cadherin–catenin–actin complex via capping protein inhibition. The loss of CRAD inhibits F-actin polymerization and subsequently disrupts the cadherin–catenin–actin complex, which leads to β-catenin release and Wnt signalling hyperactivation. In mice, CRAD knockout induces epithelial cell integrity loss and Wnt signalling activation, resulting in the development of intestinal mucinous adenoma. WithAPC mutation, CRAD knockout initiates and accelerates mucinous and invasive adenoma development in the colorectum. These results define CRAD as a tumour suppressor, the inactivation of which deregulates the cytoskeleton and hyperactivates Wnt signalling thus initiating mucinous colorectal cancer. Our study reveals the unexpected roles of an actin cytoskeletal regulator in maintaining epithelial cell integrity and suppressing tumorigenesis. Jung et al. demonstrate that loss of CRAD impairs F-actin polymerization and disrupts the cadherin–catenin–actin complex, thereby hyperactivating Wnt signalling and promoting mucinous intestinal tumorigenesis.